Childhood resilient personality trajectories and associations with developmental trajectories of behavioral, social-emotional, and academic outcomes across childhood and adolescence: A longitudinal study across 12 years. (July 2021) - Shi, Qinxin; Liew, Jeffrey; Ettekal, Idean; Woltering, Steven
Abstract: This study examined the continuity and change of childhood resilient personality (first three years in primary education), and how differential trajectories in resilient personality were dynamically associated with behavioral problems, social-emotional functioning and academic performance across the primary and secondary school years (Grade 1–12). Participants were 784 academically at-risk students predominantly from low SES families (47% girls, 37.4% Latino or Hispanic, 34.1% European American, and 23.2% African American) who were recruited in grade 1 (Mean age = 6.57) and followed annually through the final year of high school (Grade 12). Results revealed three distinct trajectories of childhood resilient personality, including an ego-resilient or flexible group (26.8%), an ego-brittle or inflexible group (21.9%), and an ordinary or common group (49.9%). Children in the ego-brittle group were at a greater risk for sustaining high levels of behavioral problems, low socio-emotional functioning (based on parent and teacher report), and poor academic performance across formal schooling. In contrast, the resilient children exhibited persistently low behavioral problems, high social-emotional functioning, and better academic performance across formal schooling. Findings also indicated that the protective effect of childhood resiliency was sustained even after the transition from childhood to adolescence. Highlights: Three subtypes of resilient personality trajectories were identified. The three trajectories exhibited absolute (mean-level) stability in childhood. Ego-brittle subtype was most vulnerable to developmental and academic problems. Ego-resilient subtype was most protected from developmental and academic problems. Group differences in adjustment outcomes were found with developmental transitions.